Status Kesuburan Berdasarkan Fitoplankton Di Perairan Danau Waren, Tual - Utami, Endang Sri; Fitrinawati, Henny (Sekolah Tinggi Pertanian Kutai Timur, 2025)
Lake Waren is an important lotic in Tual City, playing a crucial role in maintaining ecological balance, a habitat for flora-fauna aquatic, a hydrological cycle, and an area for fish spawning and growth. However, human activities (domestic wastel, tourism activities) increase nutrient levels (N and P) which triggers eutrophication and impacts water quality degradation, changes in phytoplankton composition, and disruption of food chain. Phytoplankton composition and abundance can describe the trophic status (oligotrophic, mesotrophic, eutrophic). Therefore, monitoring water through phytoplankton analysis and organic pollution levels is important to maintain ecosystem balance and ecological sustainability, especially for fisheries. Plankton sampling was conducted at five stations for three observations over two weeks. Plankton samples obtained from plankton net were given 2-3 drops of Lugol as preservation, then observed under a microscope using Sedwick-Rafter Counting Cell (SRC). The results of the plankton analysis explained that Lake Waren has a eutrophic status (IN = 7.7) and indicated organic matter contamination (IP = 15). The aquatic ecosystem is in a stable condition and has good resilience ability, with no dominance of certain plankton species described from medium diversity (phytoplankton 1.7096 - 2.3044; zooplankton 0.8587 - 1.6406), high uniformity (phytoplankton 0.9006 - 0.9610; zooplankton 0.7156 - 1.0194), and low dominance (phytoplankton 0.1070 - 0.2039; zooplankton 0.2093 - 0.4793). This condition is supported by water quality parameters according to quality standards for the life of freshwater biota, namely temperature (30 - 32oC), pH (8.2 - 8.6), DO (4 - 6.5 mg/L), and brightness (80 - 130 cm).